Psychometric properties of a Serbian version of the State-Trait Anxiety Inventory X-2 - Damjan Jakšić; Jovana Trbojević Jocić; Stefan Maričić; • Bülent Okan Miçooğulları (Exercise and Quality of Life)
Given that anxiety is a significant individual disposition that affects sports performance, this study aimed to verify the latent variables obtained by the State – Trait Anxiety Inventory X-2, and to compare the obtained factor solutions with the proposed model of latent variables. The second aim refers to the presentation of the results of the questionnaire State – Trait Anxiety Inventory X-2 answered by Serbian male and female handball players. The research was conducted on a sample of 170 respondents, 99 male and 71 female handball players, aged 14 to 39 years (average age = 21.9) with an average handball playing career of 9.39 years. Towards the end of 2019, the respondents filled in the above-mentioned questionnaire used to assess anxiety as a personality trait. Exploratory factor analysis with certain modifications of the algorithm was applied to determine accurately latent space. The overall analysis was performed using the R statistical package. Four factors were selected based on the conducted factor analysis of the latent space of the questionnaire. Ten, five, three and two items are projected on the first, second, third and fourth factor respectively. Since internal reliability of the fourth factor was 0.394 it was excluded from further consideration and interpretation. The achieved scores on four separate factors show that Serbian male and female handball players achieve average results on the first (Presence of Trait anxiety) and the third factor (Absence of proactivity), while they achieve scores above the average on the second factor (Positive affect). In order to examine the sex differences between the examined variables, a one-way analysis of variance was performed. The findings show that there is no statistically significant difference on all three factors between the scores achieved by male and female handball players. A statistically significant difference between handball players of different competitive ranks appeared only on the Positive affect factor between the top athletes and the athletes in the second league (p = .04).